2001
DOI: 10.1099/0022-1317-50-6-509
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Legionella pneumophila antigen in urine samples by the BinaxNOW immunochromatographic assay and comparison with both Binax Legionella Urinary Enzyme Immunoassay (EIA) and Biotest Legionella Urin Antigen EIA

Abstract: The new BinaxNOW Immunochromatographic (ICT) Assay for the detection of Legionella pneumophila antigens was used to test 535 urine specimens from patients with and without Legionnaires' disease. The speci®city, calculated by testing 112 samples from patients with pneumonia of aetiologies other than Legionella infection, and 167 urine specimens from urinary tract infections, was found to be 97.1% if the manufacturer's guidelines were followed. However, it was determined that the`false positive' results characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 8 publications
2
80
0
12
Order By: Relevance
“…By contrast, the Binax NOW ICT was significantly less sensitive than the EIAs, detecting only 37% of the cases. We did not expect to find such a large difference, since previous studies have shown that the sensitivity levels of both tests (the ICT and the EIAs) are approximately the same (8,14). In spite of this, our findings are in agreement with those of Dominguez et al (2), who observed that the sensitivity of the ICT assay using nonconcentrated samples was 55.5% relative to the EIA results; after concentration of the urine, the sensitivity levels of the two methods (EIA and ICT) were the same.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, the Binax NOW ICT was significantly less sensitive than the EIAs, detecting only 37% of the cases. We did not expect to find such a large difference, since previous studies have shown that the sensitivity levels of both tests (the ICT and the EIAs) are approximately the same (8,14). In spite of this, our findings are in agreement with those of Dominguez et al (2), who observed that the sensitivity of the ICT assay using nonconcentrated samples was 55.5% relative to the EIA results; after concentration of the urine, the sensitivity levels of the two methods (EIA and ICT) were the same.…”
mentioning
confidence: 95%
“…The differences in sensitivity levels for the three tests were not significant (P ϭ 0.2). Multiple com-parisons of the commercially available kits have been previously published (5,7,8). None of these previous studies were reported to have demonstrated significant differences in the abilities of the different tests to detect L. pneumophila antigen in urine.…”
mentioning
confidence: 99%
“…18,19 Streptococcus pneumoniae and Legionella pneumophila serogroup 1 antigens in urine were tested by immunochromatography. 20,21 Causative pathogens of pneumonia met one of the following criteria: sputum Gram stain showing phagocytic cells and bacteria equivalent to 10 3 -10 5 colony-forming units (CFU)/ml in sputum culture; >10 6 CFU/ml bacteria in the sputum culture; blood culture-positive; positive urinary pneumococcal or urinary Legionella antigen-test results; positive antibody titers against M. pneumoniae and C. pneumoniae.…”
Section: Microbiological Investigationmentioning
confidence: 99%
“…However, in routine and clinical laboratory work, legionellosis is rarely proven by culture whereas detection of urinary antigen is now common (6,14). All commercially available assays, except the Biotest enzyme immunoassay (EIA) (Dreieich, Germany), are marketed by their manufacturers as kits for the detection of L. pneumophila serogroup (sg) 1 urinary antigen, but some recent studies have shown that in practice the sensitivities of these assays ranged from 14 to 65% for non-sg 1 infection (1,9,10,12). None of these studies, however, provide information on the clinical utility of urinary antigen detection for the diagnosis of community acquired, travel-associated, and nosocomial Legionnaires' disease with regard to the distribution of serotypes among these categories of infections.…”
mentioning
confidence: 99%